A Case Series of Unexplained Somatic Symptoms of Gilhari Syndrome - A Culture-bound Syndrome and Review - Sharma, Mini; Chanchlani, Veerbhan; Kumari, Kanchan; Vaishnav, Jairaj Kumar (Archives of Case Reports, 2025)
Culture plays an important role in shaping the emotional & behavioral expression of a person. Many times, our beliefs color the psychological and somatic symptoms of psychiatric illness as seen in various culture-bound syndromes. We are describing 3 cases of one such culture-bound syndrome called Gilhari syndrome. In the management of these cases, special consideration to phenomenology is needed along with consultation and liaison with various specialties.